Effect of different silica coatings on the toxicity of upconversion nanoparticles on RAW 264.7 macrophage cells - Kembuan, Cynthia; Oliveira, Helena; Graf, Christina (Beilstein Journal of Nanotechnology, 2021)
Upconversion nanoparticles (UCNPs), consisting of NaYF4 doped with 18% Yb and 2% Er, were coated with microporous silica shells with thickness values of 7 ± 2 and 21 ± 3 nm. Subsequently, the negatively charged particles were functionalized with N-(6-aminohexyl)-3-aminopropyltrimethoxysilane (AHAPS), which provide a positive charge to the nanoparticle surface. Inductively coupled plasma optical emission spectrometry (ICP-OES) measurements revealed that, over the course of 24h, particles with thicker shells release fewer lanthanide ions than particles with thinner shells. However, even a 21 ± 3 nm thick silica layer does not entirely block the disintegration process of the UCNPs. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays and cell cytometry measurements performed on macrophages (RAW 264.7 cells) indicate that cells treated with amino-functionalized particles with a thicker silica shell have a higher viability than those incubated with UCNPs with a thinner silica shell, even if more particles with a thicker shell are taken up. This effect is less significant for negatively charged particles. Cell cycle analyses with amino-functionalized particles also confirm that thicker silica shells reduce cytotoxicity. Thus, growing silica shells to a sufficient thickness is a simple approach to minimize the cytotoxicity of UCNPs.
Keywords: cytotoxicity; ion release; RAW 264.7 macrophage cell line; silica coating; upconversion nanoparticles